INTERACTION BETWEEN EDUCATION AND ECONOMIC GROWTH: TRAINING FOR TEACHERS AND STUDENTS - Sariwulan, Rd Tuty; Pratama, Aditya; Saptono, Ari; Sudiarditha, I Ketut R (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
Education plays a strategic role in supporting sustainable economic growth. Teachers and students often lack a deep understanding of how education can drive economic growth through the development of relevant skills, innovation, and entrepreneurship. This training aims to improve teachers' and students' understanding of the relationship between education and economic growth. Using information related to economic growth as a source of learning materials can train teachers in developing learning strategies based on current sources. This activity also equips students with an understanding that economic growth can be used as a source of information to improve practical skills that can enhance their competitiveness in the workplace and can use economic growth as case study material. Furthermore, this training also aims to facilitate collaboration between educational institutions, businesses, and industry to create a more applicable learning ecosystem oriented to job market needs.